2005
DOI: 10.1117/12.597429
|View full text |Cite
|
Sign up to set email alerts
|

Methods study for the relocation of visual information in central scotoma cases

Abstract: In this study we test the benefit on the reading performance of different ways to relocating the visual information present under the scotoma. The relocation (or unmasking) allows to compensate the loss of information and avoid the patient developing driving strategies not adapted for the reading. Eighty healthy subjects were tested on a reading task, on each a central scotoma of various sizes was simulated. We then evaluate the reading speed (words/min) during three visual information relocation methods: all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The image deformation disrupts low and high level of recognition processes reducing visual performance. Our first experiment have shown that visual performance obtained with this new system is very sensitive to the way masked signal is make visible [18]. Our best condition is observed when displayed signal translates human optimal cognitive processes.…”
Section: Signal Restitutionmentioning
confidence: 78%
See 1 more Smart Citation
“…The image deformation disrupts low and high level of recognition processes reducing visual performance. Our first experiment have shown that visual performance obtained with this new system is very sensitive to the way masked signal is make visible [18]. Our best condition is observed when displayed signal translates human optimal cognitive processes.…”
Section: Signal Restitutionmentioning
confidence: 78%
“…When patient fixates zone of interest in the text, all visual signal masked under the scotoma is visible outside the scotoma. This new visual signal display limits visual signal search and improve signal location and comprehension [18].…”
Section: Application Examplesmentioning
confidence: 99%
“…The majority of participants trialing this technique were normally sighted with simulated central scotomas, but two had central field loss (CFL). [58][59][60][61] A modest improvement in reading rate was found in both groups. This may encourage others to update this work with the advances in technology made since its publication, perhaps allowing time for perceptual adaptation.…”
Section: Remapping and Retargetingmentioning
confidence: 86%